Development of Children's Literature Book Based on Primary School Students’ Ecoliteration - Hartati, Tatat; Andriani, Eli Nurlela; Supriatna, Nana; Nuriyanti, Risma (Universitas Sebelas Maret, 2021)
Lack of student interest in literature is due to the low literacy of students. Therefore, one of the ways to improve the students’ literacy and ecological awareness is through children's literature . Hence, Ecoliteration-based children's literature books are considered to be used as learning support books, media as well as sources of learning Bahasa for elementary schools .This study aimed to determine the design of eco-literation-based children's literature models for elementary school students.. This study adopted a development research wich Educational Design Research (EDR) was applied. This study involved lecturers, practitioners/ experts, and elementary school, teachers. The developed book contained some materials namely Bahasa, Science, and Social Sciences for four grade students by proposing a theme of